Uso da região espectral de sobretons para determinação do teor de biodiesel e classificação de misturas diesel/biodiesel adulteradas com óleo vegetal - Vasconcelos, Fernanda Vera Cruz de (2011)
This work evaluates the use of overtone regions (NIR) for the classification and determination of biodiesel content in diesel/biodiesel blends adulterated with vegetable oil. For this purpose, NIR spectra were obtained using three different optical paths: 1.0 mm (9000-4000 cm-1); 10 mm (9000-6300 cm-1) e 50 mm (7500-6300 cm-1). Principal Component Analysis (PCA) and Linear Discriminant Analysis (LDA) with the Successive Projections Algorithm (SPA) were employed to build screening models to identify adulteration of diesel/biodiesel blends with vegetable oils. The multivariate calibration models (Partial Least Square - PLS, Partial Least Square with significant regression coefficients selected by Jack-Knife algorithm - PLS/JK and Multiple Regression Linear with variable selection by Successive Projections Algorithm - MLR/SPA) were developed to determine the biodiesel content. The results showed that the overtone regions with the classification strategy LDA/SPA can be used in preliminary studies to detect adulteration of diesel/biodiesel blends with vegetable oil. This strategy showed positive results for classifying, with a correct classification rate of 86% for the optical paths of 10 mm and 50 mm. In addition, the work demonstrated the potential of overtone regions with MLR/SPA regression strategy to determine biodiesel content in diesel/biodiesel blends, in the range from 0.0% to 10.0%v/v, considering the possible presence of raw oil as a contaminant. This strategy is simple, fast and uses a fewer number of spectral variables. Considering this, the overtone regions can be usefull to develop low cost instruments for the quality control of diesel/biodiesel blends, considering the lower cost of optical components for this spectral region.